Building Peace in South East Europe : Macroeconomic Policies and Structural Reforms Since the Kosovo Conflict. (World Bank Group, 2002)
A copublication of the World Bank and the International Monetary Fund; Prior to the eruption of the Kosovo conflict in the spring of 1999, the countries of South Eastern Europe - Albania, Bosnia and Herzegovina, Bulgaria, Croatia, FYR Macedonia, Romania, and FR Yugoslavia - were lagging behind those of Central Europe and the Baltics from an economic and governance perspective. Although short lived, the crisis threatened all countries in the region and thus, it became a defining moment for them. The approach developed by the interrational community in response to the crises, was a fully integrated one, which included reconstruction and economic prosperity for the entire region. This paper documents the progress made by the region in terms of economic growth and government reform. It acknowledges the positive impact of the donor community upon this progress and points out that ongoing progress depends upon effective governance and policy development from the authorities in the region. This is critical to bringing private investment into the region.